Keterlambatan Keberangkatan Kapal Penumpang Semi Kontainer : Studi Kasus Di KM Nggapulu - Cassaluna, Vennera; Arifin, Moh. Zaenal; Sari, Ria Hermina (Dinamika Bahari, 2024)
Departure schedule is an important thing to be considered by the companies and ship crews providing passenger ship. KM Nggapulu experienced a delay in departure at Fak-Fak Port on January 26, 2023. This raised complaints from passengers due to their inconvenience. This study aims to analyze the problem of departure delay of KM Nggapulu by identifying the factors and impacts of the delays, as well as actions to prevent delays in passenger ship. Qualitative method using fishbone analysis was applied in this research. Data were collected through observation, interviews, documentation studies, and literature studies. To test the validity of the data, researchers used triangulation. The research found that the delay in departure of KM Nggapulu is due to the late loading of containers. This occurred due to the negligence of the container loading and unloading party and the lack of coordination between PT SBN, the owner of the goods (shipper), and the ship’s crew. The delay of containers loading resulted in the ship's delayed departure for 5 (five) hours and caused complaints from passengers. Optimizing coordination between related parties, increasing manpower, and optimizing loading and unloading facilities at the port were the actions taken to prevent the delay.